ANALISIS KELEMBAGAAN PENGEMBANGAN HUTAN ADAT DESA TORO KECAMATAN KULAWI KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Berwin, Berwin; Golar, Golar; Sustri, Sustri (Warta Rimba, 2014)
This research aimed to revitalizethe local institution and its implication on the management of natural resources in Lore Lindu National Park area. The research was conducted at the village of Toro, Kulawi district, Sigi Regency, Central Sulawesi, from October through December 2013. The method used in this study is the method of historical and institutional analysis and qualitative approach by interview process on key informants as respondents.The results showed that institutional revitalization was influenced by community needs on institution development caused social dynamics and community economy. New institutional revitalization has implication on structure and regulation change of local institution of Toro village. Institution in Toro was contributed by local leadership role particularly in determination of natural resources and social economy. Keywords: Institution Analysis, Development, Community Forest, Toro Community.